Diapycnal Mixing in the Ocean: From Dissipation Scale to Large Scale Meridional Overturning Circulation - Mashayekhi, Alireza
In this thesis we will investigate the role of diapycnal mixing on the ocean general circulation. This thesis is divided into three main parts. In the first part we show that there exists an almost infinite number of pathways to turbulence in oceanic energetic shear zones at high Reynolds number. Such a large number of accessible routes to truly chaotic motion is not typical of most of the existing body of laboratory and numerical experiments of shear-induced diapycnal mixing, but is shown to be of relevance to diapycnal mixing in geophysical flows. A key finding is that the use of generally accepted empirical relations based on laboratory experiments for the quantification of diapycnal mixing leads to large inaccuracies. In the second part we perform high resolution numerical experiments of diapycnal mixing in the oceanographically relevant high Reynolds number parameter range. Through detailed analysis of the flow energetics and mixing properties of these flows, we show that the net buoyancy flux facilitated by turbulence, the efficiency of diapycnal mixing, and the resultant effective diffusivity, all depend in non-trivial ways on the specific route to turbulence for each individual mixing event. This has important implications for practical methods of estimating an effective diapycnal mixing diffusivity from observations as well as for parametrization of mixing in ocean general circulation models. We show quantitatively that such methods can be inaccurate to the extent that they will need to be completely revised or replaced. In the third and final part of the thesis we investigate the sensitivity of the meridional overturning circulation of the abyssal ocean to the intensity and spatial variations of diapycnal mixing. We show that changes in intensity of mixing by factors well within the errors associated with practical estimates (as discussed above) lead to significant changes in ocean circulation. We show that enhanced abyssal mixing, surface winds, and meso-scale eddies play leading roles in driving the abyssal ocean circulation and in setting the stratification. As an example of the application of our analysis we show that proper parametrization of enhanced abyssal mixing leads to realization of the important role of the (often neglected) geothermal heat flux in driving the Antarctic Bottom Water circulation. PhD